การเตรียมและศึกษาลักษณะเฉพาะของฟิล์มบางโครเมียมไนไตรด์ที่เคลือบ ด้วยรีแอคทีฟดีซีอันบาลานซ์แมกนีตรอนสปัตเตอริง Preparation and Characterization of CrN Thin Films Deposited by Reactive DC Unbalanced Magnetron Sputtering - วิทิตอนันต์ นิรันดร์; วรรณทวี กรรณิการ์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ ฟิล์มบางโครเมียมไนไตรด์ (CrN) เคลือบบนซิลิกอนด้วยวิธีรีแอคทีฟดีซีอันบาลานซ์แมกนีตรอนสปัตเตอริง เพื่อศึกษาผลของอัตราไหลแกส๊ ไนโตรเจนในชว่ ง 2.5 - 10.0 sccm ตอ่ โครงสรา้ งของฟลิ ม์ บางที่เคลือบได้ โดยโครงสร้างผลึก ความหนา ความหยาบผิว ลักษณะพื้นผิวและองค์ประกอบทางเคมีของฟิล์มศึกษา ด้วยเทคนิค XRD, AFM, FE-SEM และ EDS ตามลำดับ ผลการศึกษาพบว่า โครงสร้างผลึกของฟิล์มบาง ที่ได้สอดคล้องกับโครเมียมไนไตรด์ระนาบ (111) และ (200) โดยความเป็นผลึกของฟิล์มที่เคลือบได้แปร ตามอัตราไหลแกส๊ ไนโตรเจน ขนาดผลึกมีคา่ ลดลงจาก 34.2 nm เปน็ 14.3 nm เมื่ออัตราไหลแกส๊ ไนโตรเจน เพิ่มขึ้น สำหรับลักษณะพื้นผิว ความหนาและความหยาบผิวของฟลิ ม์ ที่เคลือบไดพ้ บวา่ แปรคา่ ตามอัตราไหล แกส๊ ไนโตรเจน โดยความหนาและความหยาบผิวมีคา่ ในชว่ ง 412 - 515 nm และ 0.8 - 1.2 nm ทั้งนี้ฟลิ ม์ บาง ที่เคลือบไดท้ ั้งหมดมีโครเมียมและไนโตรเจนเปน็ สว่ นประกอบในอัตราสว่ นตา่ ง ๆ ซึ่งแปรคา่ ตามอัตราไหล แก๊สไนโตรเจน Abstract Chromium nitride (CrN) thin films were deposited on silicon by reactive DC unbalanced magnetron sputtering method. The effect of N2 gas flow rate, in the range of 2.5 - 10.0 sccm, on the structure of the as-deposited thin films was investigated. The crystal structure, thickness, roughness, surface morphology and elemental composition were characterized by XRD, AFM, FE-SEM and EDS. The results showed that the crystalline structure of the as-deposited films corresponded to the chromium nitride in (111) and (200) plane. The crystallinity of the as-deposited films was varied with the N2 gas flow rate. The crystallite size decreased from 34.2 nm to 14.3 nm with increasing the N2 gas flow rate. The surface morphology, thickness and roughness were seen to vary with the N2 gas flow rate. Thickness and roughness were in the range of 412 - 515 nm and 0.8 - 1.2 nm, respectively. The as-deposited films compose of chromium and nitrogen in different ratios depending on the N2 gas flow rate.